PENGARUH PERENCANAAN PAJAK,BEBAN PAJAK TANGGUHAN,DAN KUALITAS LABA TERHADAP NILAI PERUSAHAAN: Studi Empiris pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Apriia harahap, Syavira; Rima Prasetya, Eka (Perwira Journal of Economics & Business, 2023)
This research aims to prove empirically regarding the Effect of Tax Planning, Deferred Tax Expenses, Earnings Quality on Firm Value. In this study the independent variables used were tax planning, deferred tax expense and earnings quality, while the dependent variable used was firm value. This research was conducted by taking a sample of property & real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The type of data used in this research is quantitative data and secondary data in the form of annual reports that have been audited and published on the Indonesia Stock Exchange (IDX) from 2016-2021. The samples were collected by purposive sampling method with 15 companies being sampled with a 5 year research period, thus obtaining a total of 75 company samples. Data processing using Microsoft Office Program and Eviews 9 Statistical Program by analyzing descriptive statistics, panel data regression model test, classical assumption test, coefficient of determination, panel data regression analysis, T statistical test and F statistical test. T statistical test results show that variable Profit Quality has a significant effect on Firm Value, while Tax Planning and Deferred Tax Expenses have no effect on Firm Value. The results of the F test show that tax planning, deferred tax expense and earnings quality have a simultaneous effect on firm value..